1998
DOI: 10.1007/s005420050104
|View full text |Cite
|
Sign up to set email alerts
|

New development strategies for high aspect ratio microstructures

Abstract: In the first step of the LIGA process a resist layer, typically PMMA (polymethylmethacrylate), is pattered by deep X-ray lithography. The exposed parts are subsequently dissolved by an organic developer. The quality and the achievable height of the microstructure is decisively determined by the development process. In order to increase the aspect ratio and maintain the quality of the microstructures the parameters influencing the development process were investigated. In the case of dip development and ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…The megasonic supported development of LIGA microstructures was first suggested and investigated by Zanghellini et al [2,5]. It was shown that the megasonic agitation increases the development rate and that the development rate depends on both the lateral form of the structures and the acoustical intensity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The megasonic supported development of LIGA microstructures was first suggested and investigated by Zanghellini et al [2,5]. It was shown that the megasonic agitation increases the development rate and that the development rate depends on both the lateral form of the structures and the acoustical intensity.…”
Section: Introductionmentioning
confidence: 98%
“…How sensitive are the effects to probe location with respect to the megasonic source? Why do the same kind of structures on a single substrate show considerable deviations in the developed depth [5]? What benefits can megasonic agitation bring for electroforming?…”
Section: Introductionmentioning
confidence: 98%
“…Another method, using a needle to measure the removal rate of the exposed material, does not allow classifying the removed gel-layer thickness, additionally the method does not provide measurements of smaller microstructures then the needle diameter which was 30 mm in Refs. [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…Acoustic agitation offers a promising approach to enhance the mass transport rates within HARMS (Zanghellini et al 1998). Previous research has shown that ultrasonic agitation may change a diffusion controlled electrodeposition process into a charge controlled one (Hyde et al 2002).…”
Section: Introductionmentioning
confidence: 99%